THE LEGITIMAZATION OF VIOLENCE AGAINST THE AHMADIYYA COMMUNITY IN INDONESIA - Torhild Breidlid (Universitas Gadjah Mada, 2013)
The Ahmadiyah community in Indonesia has experienced increasing infringement on their religiousfreedom in various forms during the last ten years. The opening up of democracy in 1998 resultedin the involvement of “non state actors “in religious violence. Despite increasing attacks against theAhmadiyah community, the state has been reluctant to prevent or punish religious attacks against theAhmadiyah community. In this article I argue that violence against the Ahmadiyah is in danger ofbecoming legitimate.